Science goals for a high-frequency radar and radio imaging array - Isham, Brett; Bullett, Terence; Gustavsson, Björn; Polisensky, Emil; Brum, Christiano; Fallen, Christopher; Belyey, Vasyl; Parra-Rojas, Francisco; Norouzi, Leila; Stramkals, Arturs; Ökten, Mehmet Baran (Frontiers in Astronomy and Space Sciences, 2023)
A medium and high frequency antenna array for radar and radio imaging of the ionosphere is planned for installation in Aguadilla, Puerto Rico. Science goals include the study of space weather, radio propagation, meteors, lightning, and plasma physics. Radio imaging is ideal for the study of stimulated ionospheric radio emissions, such as those induced by the Arecibo Observatory high-power HF radio transmitter, which is likely to be restored to operation in the near future. The array will be complemented by a wide variety of instruments fielded by collaborators, and will be a rich source of student projects at all levels.